ANALYSIS OF THE CYSTOCARP DEVELOPMENT OF SEAWEED (Kappaphycus alvarezii) ON MEDIA ENRICHED WITH A COMBINATION OF NITROGEN AND PHOSPHATE - Muhammad Sahir; Rustam; Gunarto Latama; Isma Riskiani (Hasanuddin University, 2022)
Seaweed (Kappaphycus alvarezii), in terms of providing seeds in cultivation activities, is still carried out vegetatively, namely cutting the thallus (cuttings), which is then cultivated until it is ready to be harvested (Rao & Reddy, 1997). However, such a method will experience problems, especially the provision of quality seeds on a large scale, and it does not depend on the season. The possible alternative to do is by generative seeding method. K. alvarezii can be developed for cultivation by utilizing the nature of generative reproduction through the development of carpospores, characterised by cystocarps on the surface of the thallus. However, the cystocarp that has been formed needs nutrients in the development process to produce spores of good quality and quantity. Nutrients that are needed to support cystocarp development include nitrogen and phosphate. The benefits of nitrogen and phosphate for seaweed growth cannot be replaced with other elements. This is due to the role of nitrogen as a constituent of protein and phosphate as an energy provider. This study aimed to determine the optimum nitrogen and phosphate enrichment ratio for cystocarp development. The research was carried out from November 2018 to February 2019 at the Seaweed Laboratory of the Takalar Brackish Aquaculture Fisheries Center (BPBAPT). The research location is Mappakalompo Village, Galesong District, Takalar Regency, South Sulawesi Province. They were analyzed at the water quality laboratory of Hasanuddin University to analyse the N and P content in the media. There were 6 treatments with 3 replications each, namely Treatment A: Without enrichment (SW), Treatment B: 1N=0.5 ppm: 1P=0.5 ppm, Treatment C: 2N=1 ppm: 1P= 0,5 ppm, Treatment D : 3N=1,5 ppm : 1P=0,5 ppm, Treatment E : 1N=0,5 ppm: 2P = 1 ppm, and Treatment F : 1N=0,5 ppm : 3P = 1.5 ppm. The results showed that the development of a shorter cystocarp phase was found in treatment D, which was 14 days. Meanwhile, treatment with a long time of 17 days occurred in treatment A (SW).